Novos espécimens de susisuchus anatoceps salisbury, frey, martill & buchy 2003 do grupo Santana, Bacia do Araripe - Leite, Karla Janaisa Gonçalves (2017)
New specimens of Susisuchusanatocepsfrom the Santana Group of Lower Cretaceous are described, bringing new information that helps in understanding the geological and evolutionary history of the neosuchians and eusuchians. The methodological procedures consisted of a mechanical preparation and morphological description of the specimens, comparison with other specimens of Susisuchidae and a phylogenetic analysisof this clade. The phylogenetic analysis used data already available in the literature and the TNT software for cladistic analysis. With the new specimens of Susisuchus, new morphological characteristics of the species were known. The first specimen of Susisuchus(FPH-243-V) preserved in the ventral view distinctly shows the position of the coana completely located in the pterygoid. Phylogenetic analysis links Susisuchusto Isisfordiain a monophyletic group, Susisuchidae. The position of this clade as advanced neosuchian changes with the coding of new ventral characters of the Susisuchusskull, the group is placed in Eusuchia.